Challenges Faced and Employability Skills that Employers Seek in Fresh Graduates in a Third World Country - Wafa, Ahmadzia; Singh Kartar Singh, Jugindar; Kaur Sarjit Singh, Devinder (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study was to find out what kind of skills fresh graduates need to have when enteringthe job market in a third world and highrisk country. In addition, this study also explored the challenges faced by HR managers in a war torn country. The research was carried out by using the qualitative research method. The data was gathered by using semi-structured interviews with open-ended questions designed to answer to the research questions. Nine Human Resource managers were interviewed based on a list of questions. The key finding was that soft skills that encompass communication and problem solving are the most sought after in the workplace. It is suggested that the Higher Education Institutions collaborate and work closely with employers to minimize the skill gap. Having the knowledge of what employability skills that are key for HRM graduates can help minimize the skills gap and assist educators in producing employable graduates.